2020
DOI: 10.1002/jsfa.10655
|View full text |Cite
|
Sign up to set email alerts
|

Kaolin, Ascophyllum nodosum and salicylic acid mitigate effects of summer stress improving hazelnut quality

Abstract: BACKGROUND: Various strategies are needed to mitigate the negative impact on or to increase fruit quality. The effect of spraying kaolin (K), Ascophyllum nodosum (An) and salicylic acid (SA), in trees with and without irrigation, on quality and sensorial attributes of hazelnut (Grada de Viseu cultivar) was investigated during two consecutive years (2016 and 2017) in a commercial orchard located in Moimenta da Beira, Portugal. RESULTS: The treatments affected positively the biometric parameters nut and kernel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Recently, soybean submitted to water stress and treated with this biostimulant was able to restore its' water content while also promoting the growth of the root system, increase photosynthetic efficiency and, chlorophyll content [149]. Additionally, A. nodosum SWE was shown to improve the response of Corylus avellana trees to heat and drought stress, while preserving the quality of the kernel [150,151]. In fact, nut and kernel biometric parameters increased in comparison to control, alongside the concentration in vitamin E, phenolics and antioxidant activity.…”
Section: Ascophyllum Nodosummentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, soybean submitted to water stress and treated with this biostimulant was able to restore its' water content while also promoting the growth of the root system, increase photosynthetic efficiency and, chlorophyll content [149]. Additionally, A. nodosum SWE was shown to improve the response of Corylus avellana trees to heat and drought stress, while preserving the quality of the kernel [150,151]. In fact, nut and kernel biometric parameters increased in comparison to control, alongside the concentration in vitamin E, phenolics and antioxidant activity.…”
Section: Ascophyllum Nodosummentioning
confidence: 99%
“…Increased plant RWC and CO 2 assimilation; improved plant water use efficiency; reduced electrolyte leakage, membrane lipid peroxidation, antioxidant enzymes and proline content; increased fruit biometric parameters, antioxidant activity vitamin E, soluble sugars and phenolics content. [150,151] Glycine max L.…”
Section: Corylus Avellanamentioning
confidence: 99%
“…The increase in antioxidant capacity due to the application of kaolin was also observed by Dinis et al [ 40 ]; the authors investigated this effect by studying changes in the enzymatic and nonenzymatic antioxidant systems in leaves and berries of grapevine under summer stress. No significant effects of kaolin treatment were observed by Cosìc et al [ 41 ] on sweet peppers, whereas kaolin treatments positively affected the antioxidant activity and contents of some individual phenolics on hazelnut, in trees with and without irrigation [ 42 ]. Finally, a 6% kaolin spray was effective in improving the contents of phenolics and flavonoids, and the antioxidant enzyme activity of mango fruits [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the agronomical level, a number of commercial seaweed extract products are available, and several studies have shown their good results [ 92 ]. Brown seaweeds are the most used type in agriculture, Ascophyllum nodosum L. being the most studied [ 49 , 50 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Some studies in Vitis vinifera have shown that foliar application is beneficial to control and prevent the impacts of biotic and abiotic stress (see Table 1 ).…”
Section: Biostimulants Used In Grapevinementioning
confidence: 99%